Gender differences in anaphylaxis. Issue 5 (October 2019) - Salvati, Lorenzo; Vitiello, Gianfranco; Parronchi, Paola
Abstract : Purpose of review: Is sexual dimorphism also true in anaphylaxis as described in other allergic diseases? Possible gender differences in the epidemiology, triggers, severity, outcomes of anaphylaxis as well as in the pathogenesis of the disease are discussed. Recent findings: Hormonal status and the X-chromosome-coded factors deeply involved in the regulation of T-cell and B-cell responses may influence the gender difference noticed in allergic diseases, such as asthma and rhinitis. Little is known if sex is also relevant for anaphylaxis, although the description of catamenial anaphylaxis is intriguing. However, epidemiologic bias, lack of reliable animal models for the human disease, differences into diagnostic codes and not harmonized clinical grading unfortunately represent hurdles to obtain meaningful information on this topic. Summary: The female sex predisposes to a dysregulation of the immune response as suggested by the increased prevalence of autoimmunity and atopy. In anaphylaxis, pathomechanisms are not fully disclosed, triggers are numerous and IgE-dependent mast cell degranulation only represents a part of the story. Improvement into the definition of the disease including a more careful coding system and better investigations about triggers seem the only way to allow a more precise assessment of the possible different risk for women to develop anaphylaxis.